Association Between Vitamin D Levels With Mdr-Tb Patients With Household Contacts And Healthy People As Comparison - Nina Herlina; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Erna Mutiara (Faculty of Medicine University of Malikussaleh, 2022)
Abstract Background: The high incidence of pulmonary tuberculosis (TB) progressing into multidrugresistant TB (MDR-TB) has become a serious concern and caused a high mortality rate. The incidence of MDR-TB was 3.3% of new cases and 20% of cases of recurrent treatment. Low levels of vitamin D is a predisposing factor of MDR-TB, and family members in contact with the patient also show risk of infection. Currently, there is no study that compares vitamin D levels between MDR-TB patients and their household contact. Method: This is a case control study, with the number of samples of each group (MDR-TB patients, household contact, healthy controls) 40 subjects, respectively. Each member of each group were checked for vitamin D levels using enzyme-linked immunosorbent assay (ELISA) technique. Result: Mean levels of vitamin D in MDR-TB patients are 32.21, contact families 31.7 and healthy controls 26.86. There is a significant relationship between vitamin D levels and MDR-TB incidence (p=0.006). Conclusion : There was no significant association between vitamin D deficiency level with MDRTB. Vitamin D insufficiency was a protective factor for MDR-TB than in healthy control.